Characterization of the magnetic switching properties of single-domain particles - Li Huang, Huei; Ju Lu, Jing (Materials chemistry and physics, 1995)
We investigated the characteristics of the magnetic switching of the single-domain particles (SDP) and studied its variation as a function of the field orientation, sweep rate, textural distribution and thermal relaxation effects. Our analysis is based on the non-interacting bi-state model using the probabilistic approach. The hysteresis loops measured at high sweep rates are much wider and the corresponding coercivities H c much larger than those taken at slower sweep rates. An increase in the field-angle orientation from the easy axis reduces the H c field, while decreasing the sweep rate flattens the trend of the variation of the curve until a very large angle is reached. The thermal factor KV/k BT, on the other hand, plays essentially the same role as the sweep rate does to the H c values: the larger the value of KV/k BT, the larger the value of H c . The transition energy barrier is roughly equal to ≈ 25 k B T if the field sweep period is 1 h, in agreement with the usual concept of the blocking temperature. However, this concept is subject to dispute if the sweep period is comparatively faster or slower. The variation of the reversible transverse susceptibility (RTS) with respect to the field orientation and thermal relaxation has also been systematically investigated. The cusps or trenches of the RTS due to thermal relaxation were shown to be substantially shaved or filled, while the corresponding H c values were shifted and reduced. The RTS of the SDPs may exhibit one, two or three prominent cusps at high values of KV/k BT depending upon the configuration and texture or randomness of the system given. The height of the cusp also varies with the field-orientation angles, and the corresponding switching-field distribution becomes broadened and decreases with the values of KV/k BT.